2014
DOI: 10.11120/elss.2014.00039
|View full text |Cite
|
Sign up to set email alerts
|

Convincing Students? Quantitative Junkies, Avoiders and Converts on a Cross-Disciplinary Course Using Quantitative Narratives

Abstract: Amidst growing concern about the shortage of social science undergraduate students with even basic quantitative methods skills, student apprehension is recognised as a barrier to learning quantitative methods. A recent ESRC-funded project has sought to overcome such fear and anxiety through the design of a cross-disciplinary social sciences unit for first-year undergraduates. The unit aimed to capture students' imaginations by the use of 'quantitative narratives' -descriptions of current social issues or contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recent, crossdisciplinary team research has outlined some structural elements needed for implementation 27 , identified effective methods for learning 28 and teaming skill characterization 29 , and offered self-efficacy measurement 30 . While applied and observational studies have examined cross-disciplinary interaction between engineering and Page 26.245.8 more removed disciplines, such as: arts, social sciences, and business [31][32][33] . This growing body of literature offers significant insight into the needs and opportunities in the crossdisciplinary space; however, more insight is needed into crossdisciplinary engineering education, teaming, and its impact on students.…”
mentioning
confidence: 99%
“…Recent, crossdisciplinary team research has outlined some structural elements needed for implementation 27 , identified effective methods for learning 28 and teaming skill characterization 29 , and offered self-efficacy measurement 30 . While applied and observational studies have examined cross-disciplinary interaction between engineering and Page 26.245.8 more removed disciplines, such as: arts, social sciences, and business [31][32][33] . This growing body of literature offers significant insight into the needs and opportunities in the crossdisciplinary space; however, more insight is needed into crossdisciplinary engineering education, teaming, and its impact on students.…”
mentioning
confidence: 99%